PENGUNAAN APLIKASI MERDEKA MENGAJAR DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA SEKOLAH PENGGERAK - Sastra Wijaya; Arita Marini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
The aim of the study to determine the effect of using the application independent teaching on the learning outcomes of fourth grade at the Palurahan 2 Public Elementary School, Pandeglang Regency which has been included in the driving school program since 2021. A total of 32 elementary school students were the samples in this study which separated into control class and experimental class. The method in research is quasi experimental (quasi experimental) using the (Nonequivalent control group design) technique through pretest and posttest instruments to see student learning outcomes. The results of the homogeneity test calculation using SPSS software version 26 for OS score Sig.0,000 ≤ α(0,05) shows the change and influence of independent teaching applications on learning outcomes which are homogeneous. The results obtained from the calculation also obtained a significance value (2-tailed) independent teaching applications on student learning outcomes showing the number 0,000 ≤ 0,05, then accept Ha and reject H0. The results of the conclusions obtained indicate that there is an influence of using independent teaching applications to improve student learning outcomes in driving schools.   Penelitian memiliki tujuan mengetahui pengaruh pengunaan aplikasi merdeka mengajar pada hasil belajar siswa kelas IV di Sekolah Dasar Negeri Palurahan 2 kabupaten pandeglang yang telah masuk dalam program sekolah penggerak sejak tahun 2021. Sebanyak 32 siswa menjadi sampel dalam penelitian ini yang dibagi kedalam kelas kontrol dan kelas eksperiman. Metode dalam penelitian dengan eksperimen semu (quasi eksperimental mengunakan teknik Nonequivalent control group design melalui instrument pretest dengan posttest unutuk melihat hasil belajar siswa. Hasil pada perhitungan uji homogenitas yang menggunakan software SPSS versi 26 for OS nilai Sig. 0,000 ≤ α (0,05) menunjukan perubah dan pengaruh aplikasi merdeka mengajar terhadap hasil belajar yang bermakna homogen. Hasil perhitungan juga diperoleh nilai signifikasi (2-tailed) aplikasi merdeka mengajar terhadap hasil belajar siswa menunjukan angka 0,000 ≤ 0,05, maka terima Ha dan tolak H0. Hasil perhitungan tersebut menyimpulkan bahwa terdapat pengaruh pengunaan aplikasi merdeka mengajar untuk meningkatkan hasil belajar siswa pada sekolah pengerak.